The Matrix of Insanity in Modern Criminal Law - Hallevy, Gabriel (Springer, 2015)
This book challenges the assumptions of modern criminal law that insanity is a natural, legally and medically defined phenomenon (covering a range of medical disorders). By doing so, it paves the way for a new perspective on insanity and can serve as the basis for a new approach to insanity in modern criminal law.